PENYULUHAN DAN BIMBINGAN PENERAPAN BAURAN PEMASARAN DALAM USAHA PENINGKATAN KUALITAS SDM TERNAK IKAN PATIN DI DESA PAGERSARI KECAMATAN KALIDAWIR KABUPATEN TULUNG AGUNG - Suseno Hendratmoko (Jurnal Pengabdian Kepada Masyarakat (J-ABDIMAS), 2018)
The community service that focused in the field of fish farming were held from July 2 to Juli 31, 2018. The method of conveying information in this activities by Educational for Sustainable Development. The effort of this community service are: The increasing of fish farmers understanding for breading management; managed integration systems of farmers and buyer-collector; communication models of fish farmers as part of information tranformation; and good coordination progress among fish farmers, especially in Pagersari vilagers.Through KKN Tematic, students with the community identifying the problems and find the solution by mobilize all the potential aspect without contrave of local wisdom. As the evaluation implementation, advocacy and collaboration with relevant parties to support the progress into better condition.